2019
DOI: 10.5935/0103-507x.20190036
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a rapid response team in a large nonprofit Brazilian hospital: improving the quality of emergency care through Plan-Do-Study-Act

Abstract: Objective To describe the implementation of a rapid response team in a large nonprofit hospital, indicating relevant issues for other initiatives in similar contexts, particularly in Latin America. Methods In general terms, the intervention consisted of three major components: (1) a tool to detect aggravation of clinical conditions in general wards; (2) the structuring of a rapid response team to attend to all patients at risk; and (3) the monitoring of indicators regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…( 6 ) After the introduction of RRTs in a large Brazilian nonprofit hospital, a significant reduction in waiting time for ICU beds among inpatients who could not be admitted immediately after indication was determined, as well as an increase in the recognition of palliative care patients; however, no difference in hospital mortality was detected. ( 19 ) Similar results were observed after the implementation of RRTs in a Brazilian university hospital, where a reduction was observed in in-hospital cardiac arrest but not in hospital mortality. ( 20 )…”
Section: Methodssupporting
confidence: 68%
“…( 6 ) After the introduction of RRTs in a large Brazilian nonprofit hospital, a significant reduction in waiting time for ICU beds among inpatients who could not be admitted immediately after indication was determined, as well as an increase in the recognition of palliative care patients; however, no difference in hospital mortality was detected. ( 19 ) Similar results were observed after the implementation of RRTs in a Brazilian university hospital, where a reduction was observed in in-hospital cardiac arrest but not in hospital mortality. ( 20 )…”
Section: Methodssupporting
confidence: 68%
“…Over the past two decades, RRT has been implemented in many secondary or tertiary hospitals in the belief that early detection and timely management of at-risk patients will improve hospital outcomes [10][11][12]. Several recent studies have demonstrated this belief by showing that RRT could help reduce in-hospital mortality rates [13][14][15][16][17][18]. In addition, RRT implementation has been shown to improve the adherence to the sepsis bundle in HOS [9].…”
Section: Introductionmentioning
confidence: 99%